Nonlinear modeling of the effect of n = 2 resonant magnetic field perturbation on peeling-ballooning modes in KSTAR. (10th January 2020) - Kim, S.K.; Pamela, S.; Kwon, O.; Becoulet, M.; Huijsmans, G.T.A.; In, Y.; Hoelzl, M.; Lee, J.H.; Kim, M.; Park, G.Y.; Kim, H. S.; Lee, Y.H.; et al.
Abstract: Using the nonlinear 3D MHD code JOREK with reduced MHD equations (visco-resistive MHD), we have successfully simulated a recent n = 2 resonant magnetic perturbation (RMP)-driven edge localized mode (ELM) suppression in KSTAR. We have found that such ELM suppression has been attributable not only to the degraded pedestal but also to the direct coupling between the peeling-ballooning mode (PBM) and RMP-driven plasma response. Notably, the pedestal pressure gradient is reduced as the radial transport is enhanced because of the formation of the stochastic layer and increased convection fluxes due to tearing and the kink-peeling mode driven by RMPs. The increased transport in the stochastic layer is due to the parallel transport across the stochastic fields, described by the Braginskii model in the simulation. While the linear stability of the PBM improves owing to the degraded pedestal, it is not a sole contributor to ELM suppression, in that the nonlinear mode coupling plays a more critical role. This outcome is consistent with previous studies where mode coupling affects the ELM mitigation or suppression. In addition, PBM locking has been numerically achieved during the ELM suppression phase, which may support the relationship between at the pedestal and the onset of ELM suppression. We suggest that PBM locking can enhance the mode interactions between RMPs and PBMs, which is significant for ELM suppression.